COVID-19 and (gender) inequality in income: the impact of discretionary policy measures in Austria - Michael Christl; Silvia De Poli; Dénes Kucsera; Hanno Lorenz (Global Labor Organization (GLO), 2021)
This paper analyzes the impact of the COVID-19 crisis on household income in Austria, using detailed administrative labor market data, in combination with micro-simulation techniques, that enable specific labor market transitions to be modeled. We find that discretionary fiscal policy measures in Austria are key to counteracting the inequality- and poverty-enhancing effect of COVID-19. Additionally, we find that females tend to experience a greater loss in terms of market income. The Austrian tax-benefit system, however, reduces this gender differences. Disposable income has dropped by around 1% for both males and females. By comparison, males profit mainly from short-time work scheme, while females profit especially from other discretionary policy measures, such as the one-off payment for children.
Keywords: D31; E24; H24; 330; COVID-19; EUROMOD; micro-simulation; STW; automatic stabilizers